The Effect of Learning Independence and the Ability to Understand Physics Concepts - Samsun, Samsun; Sarifah, Iva; Margono, Gaguk (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The Effect of Learning Independence and Digital Literacy Skills on the Understanding of Physics Concepts. This study aims to determine: 1) The effect of learning independence and digital literacy skills together on the understanding of physics concepts among students at the Health Polytechnic in South Jakarta, 2) The effect of learning independence on the understanding of physics concepts among students at the Health Polytechnic in South Jakarta, 3) The effect of digital literacy skills on the understanding of physics concepts among students at the Health Polytechnic in South Jakarta. This research is a survey study conducted at the Health Polytechnic in South Jakarta. The total population is 739 students, and a sample of 88 students was randomly selected from four study programs at the Health Polytechnic in South Jakarta. Data collection was carried out using questionnaires and tests. Data analysis was performed using descriptive statistical methods, validity tests, reliability tests, and hypothesis testing with multiple linear regression analysis using SPSS software. The results of the study prove that learning independence and digital literacy skills contribute to the understanding of physics concepts.